Association of fecal calprotectin and lipocalin-2 with subclinical intestinal inflammation and disease activity in patients with axial spondyloarthritis - Eman Abdel Ghani Sayed; Anna Abou-Raya; Mona Wagdy Ayad; Omnia Mohamed (Alexandria Journal of Medicine)
Background Axial spondyloarthropathy (axSpA) are group of diseases with inflammatory low back pain, asymmetrical oligoarthritis, HLA-B27 positivity and extra-articular manifestations. Asymptomatic subclinical gut inflammation and impaired integrity of intestinal mucosa macroscopically and microscopically can be present. Fecal calprotectin is released during neutrophilic activation and is a new marker for the inflammatory process. Lipocalin-2 is one of the mediators involved in the gut-joint axis. The association of fecal calprotectin (FCP) and lipocalin-2 (LCN-2) provide new biomarkers for disease management.Objective Was to investigate fecal calprotectin (FCP) and lipocalin-2 (LCN-2), their early relation to subclinical intestinal inflammation and disease activity in axSpA patients.Subjects Fifteen patients with axSpA diagnosed according to Spondyloarthritis International Society (ASAS) classification criteria. Fifteen healthy persons (age, sex matched) as controls.Exclusion Criteria Other autoimmune diseases as rheumatoid arthritis, cancer, HBV, HCV infection.Methods Assessment of SpA group; symptoms, onset, disease duration, course and extra-articular manifestations. Detailed history of gastrointestinal symptoms, drug history and family history. Measurement of ASDAS-ESR, ASDAS-CRP, BAS-MI, BAS-DI, BAS-FI, MASES, ASQoL, HAQ score, comorbidity assessment by BP measurement, lipid profile, kidney, liver function, FBS, 2hrPP, thyroid function tests, uric acid, ESR, CRP, HLA-B27, Plain-X ray of the affected joints. Stool analysis of FCP and LCN-2 using ELISA technique.Results ESR, CRP, HLA-B27 were higher in axSpA compared to healthy controls. FCP and LCN-2 were statistically higher in axSpA patients. Statistically significant positive correlation between FCP, LCN-2 and markers of disease activity ESR, CRP. Significant positive correlation between LCN-2 and clinical scores of disease activity ASDAS-ESR, ASDAS-CRP, BAS-DI. Colonicbiopsy revealed five patients were with colonic involvement and three were with ileal mucosal involvement.Conclusion The elevated levels of FCP and LCN-2 with intestinal inflammation indicates that FCP and LCN-2 can be used as a biomarker for monitoring disease activity in axSpA patients.